Severe eosinophilic asthma with IgG subclass deficiency treated with benralizumab and IVIG: a case report and literature review - Cakmak, Mehmet; Öztop, Nida (Alergologia Polska - Polish Journal of Allergology, 2025)
Severe asthma is characterized by poor symptom control and frequent recurrent exacerbations. Primary immunodeficiency with antibody deficiencies are the most common immunodeficiency phenotypes in adult patients and are characterized by frequent recurrent lung infections. Asthma is a common comorbid disease in primary immunodeficiency with antibody deficiencies. The case is presented here of a patient with severe eosinophilic asthma and concomitant immunoglobulin subclass deficiency who was successfully treated with benralizumab and intravenous immunoglobulin (IVIG). After 1 year of benralizumab treatment, improvements were observed in respiratory function tests. During the follow-up, fewer asthma attacks were observed and asthma symptom control improved. The IVIG treatment resulted in decreased antibiotic use for recurrent lung infections in the 1-year period. In cases of severe asthma and accompanying immunodeficiency, asthma treatment and immunodeficiency treatment should be performed together, and biological agent treatments may be required for asthma control.